Laboratory methods for the study of rod mixtures at high temperatures - S. V. Koreniugin; S. L. Rovin (Литьë и металлургия)
The article presents an analysis of laboratory methods for studying temperature and phase expansions and changes in the properties of molding and core mixtures during heating. The analysis of laboratory equipment offered on the Belarusian market for high‑temperature testing of molding materials and mixtures is carried out, the methodology for conducting such tests using devices from leading world manufacturers is described. The results of high‑temperature test tests of mixtures based on furan binders are presented.